1997
DOI: 10.1046/j.1365-2249.1997.4231441.x
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune response within the lung in HIV-1 infection

Abstract: In order to study the humoral immune defences in the respiratory tract during HIV‐1 infection, we measured the levels, local productions and anti‐HIV and antibacterial activities of IgG and IgA in the bronchoalveolar lavage fluid (BALF) and serum of 61 adult patients with severe HIV infection and of 56 HIV− controls. Albumin was used as the serum transudation factor. The increase of immunoglobulin levels in the serum of HIV‐infected patients was confirmed. The IgG level was also increased in epithelial lining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
(34 reference statements)
2
10
0
1
Order By: Relevance
“…Increased levels of IgG have also been identified in blood [59] of HIV1 women compared to low-risk subjects. Similar patterns of Ig appear in the lung [59] and the female LGT [58], with increased IgG compared to static or reduced sIgA levels.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Increased levels of IgG have also been identified in blood [59] of HIV1 women compared to low-risk subjects. Similar patterns of Ig appear in the lung [59] and the female LGT [58], with increased IgG compared to static or reduced sIgA levels.…”
Section: Discussionmentioning
confidence: 98%
“…Increased levels of IgG have also been identified in blood [59] of HIV1 women compared to low-risk subjects. Similar patterns of Ig appear in the lung [59] and the female LGT [58], with increased IgG compared to static or reduced sIgA levels. Studies on intestinal mucosa have suggested that this unexpected predominance of IgG over IgA may result from abnormal Ig production in the mucosa rather than from serum leakage [60].…”
Section: Discussionmentioning
confidence: 98%
“…An immediate freezing of sampled BAL was performed to avoid urea splitting by organisms potentially present in BAL. Using this approach, we were able to determine the initial concentration of Igs in the ELF recovered by bronchoalveolar lavage (24,30). To determine the concentration of urea recovered from BAL and serum samples, a commercially available kit (Biomerieux, Marcy l'Etoile, France) was used.…”
Section: Methodsmentioning
confidence: 99%
“…6 A substantial dysfunction of humoral immunity associated with HIV infection appears to predispose to bacterial pneumonia in these patients. 7 Previous investigators have demonstrated that penicillin is cost-effective in the treatment of lobar pneumonia before the outbreak of HIV infection in Africa. 8,9 A recent paper from India also emphasized the need for a cost-effective approach to treatment of CAP, for example with the use of parenteral penicillin in developing countries.…”
Section: Introductionmentioning
confidence: 99%